دور بعض الأساليب الوالدية في تنمية الاستقلالية لدى طفل ما قبل المدرسة بعمر (5-6) سنوات "دراسة ميدانية في محافظة اللاذقية" - ميلاد محمود; بدور سماح (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
تعدّ أساليب المعاملة التي يتبعها الوالدين في تنشئة أطفالهم من أهم العوامل التي تؤثر في نمو حاجة الاستقلالية لدى طفل ما قبل المدرسة بعمر (5-6) سنوات، ولذلك فإن دراسة هذه الأساليب ستبرز أهمية حاجة الاستقلالية، وتأثير أساليب المعاملة الوالدية في تنميتها. يتناول البحث الحالي دور بعض الأساليب الوالدية (الأسلوب الديمقراطي, الأسلوب التسلطي, الأسلوب المتساهل) في تنمية الاستقلالية لدى طفل ما قبل المدرسة بعمر (5-6) سنوات, ولتحقيق أهداف البحث تمّ تصميم استبانتين الأولى: استبانة قياس أساليب المعاملة الوالدية, والثانية استبانة قياس استقلالية طفل الروضة, وبعد الدراسة والتحليل تمّ التوصّل إلى النتائج الآتية: - توجد علاقة طردية بين الأسلوب الوالدي الديمقراطي، ونمو حاجة الاستقلالية لدى أطفال الروضة بعمر (5-6) سنوات، أي كلما كان أسلوب الوالدين ديمقراطياً أدى ذلك إلى نمو حاجة الاستقلالية لدى الأطفال. - توجد علاقة عكسية بين الأسلوبين (الوالدي المتسلط, والوالدي المتساهل)، ونمو حاجة الاستقلالية لدى أطفال الروضة بعمر (5-6) سنوات، أي كلما كان أسلوب الوالدين متسلطاً أو متساهلاً أدى ذلك إلى انخفاض نمو حاجة الاستقلالية لدى الأطفال. Methods of treatment adopted by parents in the upbringing of their children form the most important factors affecting the growth of autonomy needed in a pre-school child, so the study of these methods will highlight the importance of the need for independence, and the effect of parental treatment methods in their development. The current research addresses the role of some parenting methods (democratic, authoritarian style, lenient style) in the development of independence in a pre-school child age (5-6) years. To achieve the objectives, two questionnaires were designed: the first questionnaire measures parental methods of treatment, the second questionnaire measures independence of the kindergarten children. The study reached following results: (1) There is a positive relationship between parental democratic style, independence and the growth of need in kindergarten children, (2) There is an inverse relationship between the two approaches (authoritarian, and permissive parenting), and the growth of autonomy need to kindergarten age.